2018
DOI: 10.1017/s1368980018002306
|View full text |Cite
|
Sign up to set email alerts
|

High national and sub-national coverage of iodised salt in India: evidence from the first National Iodine and Salt Intake Survey (NISI) 2014–2015

Abstract: India is within striking reach of achieving universal salt iodisation. However, significant differentials by rural/urban, zonal and socio-economic indicators exist, warranting accelerated efforts and targeted interventions for high-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
(16 reference statements)
1
21
0
Order By: Relevance
“…Adequately iodised salt (iodine ≥15 ppm) was consumed in 77•5% of households. 7 The survey findings also showed that iodine content in most of the household salt was found around 7 ppm which was quite low as per USI standards. A country is said to have achieved USI when at least 90% of households consumed adequately iodized salt that is 15 ppm.…”
Section: Discussionmentioning
confidence: 82%
“…Adequately iodised salt (iodine ≥15 ppm) was consumed in 77•5% of households. 7 The survey findings also showed that iodine content in most of the household salt was found around 7 ppm which was quite low as per USI standards. A country is said to have achieved USI when at least 90% of households consumed adequately iodized salt that is 15 ppm.…”
Section: Discussionmentioning
confidence: 82%
“…A survey in 1998/99, when non-iodized salt was banned under the Food Adulteration Act, found household use of iodized salt to be 49 %. It fell to 30 % in 2002–2004 when there was no ban and rose to 51, 71 and 78 %, respectively, in 2005/06, 2009 and 2014/15 after the Food Standards and Safety Act came into force ( 24 ) . *…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, earning below the Saudi minimal wage also increased the odds of inadequate iodine in our non-pregnant women. Likewise, a linkage between poverty and iodine inadequacy has been reported by community studies, which could be due poor adherence of low-income populations to appropriate micronutrients and iodised salt intake [55,56]. Numerous population-based studies have also demonstrated the negative impact of smoking on thyroid functions and iodine adequacy in reproductive age and pregnant women [49,51,52,57,58].…”
Section: Discussionmentioning
confidence: 99%